ANALISIS MANAJEMEN KOPERASI DALAM MENINGKATKAN SHU (Sisa Hasil Usaha) (Kasus Koperasi Mitra Sejati Pangkalan Kuras) - Rahayu, Siti; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted at the Cooperative Mitra Sejati of Pangkalan Kuras to analyze and determine how the application of cooperative management at Mitra Sejati’s Cooperative.This research is descriptive quantitative study , the data collected in the study was obtained and separated by type, further processed and analyzed and presented in the form of frequency tables and given an explanation as appropriate. The population in this study consisted of administrators, regulatory bodies and members of the cooperative with a sampling technique using simple random sampling method. The data used are primary and secondary data, primary data is data obtained either directly from the respondent administrators, supervisors and members of the cooperative are associated with cooperative management, while secondary data are already available in the form of a brief history of the cooperative, cooperative structure and cooperative activity.From the analysis that has been done, it is known that the management of the cooperative in the form of planning, organizing, directing, coordinating and controlling conducted by the cooperative Mitra Sejati of Panggkalan Kuras In good conditions category, it is because of what has been implemented by the cooperatives are in accordance with the expectations of the board and members of cooperatives.Keywords: Cooperative Management, Planning, Organizing, Coordination, Controlling